L’apport de la carrière au modèle théorique des tâches d’adaptation à la maladie chronique: une application au cas des personnes qui vivent avec le VIH - Samson, André (Canadian Journal of Counselling and Psychotherapy, 2007)
A few years ago, a diagnosis of HIV infection could mean stopping work life, early retirement, the end of a lifestyle, or quite simply death in a fairly short time frame. However, with the advances in medicine, HIV infection is now a chronic illness that develops over the long term. The life expectancy and quality of life of people living with HIV/AIDS have improved constantly. The real challenge facing individuals living with HIV today is no longer to prepare for death but to continue to live meaningful lives with the infection. The focus must therefore be on adaptation. This article describes a theoretical model for the process of adaptation to chronic illness, the adaptive task approach, enhanced by the addition of a new adaptive task: career development.